Comparison of 2D and 3D fluoroscopy for intraoperative detection of intra-articular incongruities in distal radius fractures - Brunken, Fenna; Bullert, Benno; Grützner, Paul Alfred; Vetter, Sven Y.; Beisemann, Nils (Journal of orthopaedic surgery and research, 2025)
Background Insufficient reduction of intra-articular fractures can lead to posttraumatic arthritis. An accurate intraoperative assessment of the articular surface is essential to guide surgical decision-making. This study aims to compare the sensitivity of 2D and 3D fluoroscopy for detecting intra-articular gaps and step-offs in distal radius fractures. Methods Intra-articular distal radius fractures were induced in 6 cadaveric forearms and intra-articular incongruities(gap/step-off ) of 0, 1 and 2 mm were created using 3D-printed repositioning guides. Images were acquired by 2D and 3D fluoroscopy for each step and evaluated by 3 blinded observers. Sensitivity and specificity for the detection of intra-articular incongruities were analyzed. Additionally, the inter-rater agreement for the decision to perform revision surgery and dose area product (DAP) were evaluated. Results The overall sensitivity of 3D fluoroscopy for the detection of intra-articular incongruities was 90.28% compared to 55.56% for 2D fluoroscopy. Sensitivities for the detection of 2 mm incongruities were higher than for 1 mm especially in 2D fluoroscopy (1 mm: 38.89%; 2 mm: 74.72%). In 41.67% of cases with 1 mm incongruities where no revision was deemed necessary in 2D fluoroscopy, 3D imaging prompted a change in decision to perform revision. The dose area product was significantly higher for 3D fluoroscopy (41.87 cGycm2) compared to 2D fluoroscopy (3.13 cGycm2) (p < 0.0001).Conclusion The results suggest that 3D fluoroscopy can facilitate the detection of intra-articular incongruities in distal radius fractures and may prompt intra-operative revisions. Further clinical studies are needed to determine the effect on surgical outcomes.
Gesehen am 20.01.2026